Market Concentration and Income Inequality - Kartika, Atthahira Sastia (Gorontalo State University, 2025)
The degree of market concentration across industries has been found to have increased recently. Analysing the data on Australia's firms. This study finds that market concentration is different across sectors. Some sectors are more concentrated than others. Following market concentration, income inequality is found to be increasing in Australia. Using data for Australia from 1980-2021, this study finds a positive relationship between market concentration, measured in markups, and income inequality. In addition, this study also provides the result for the relationship between income inequality, trade openness, and automation. Lastly, this study highlights the policy implication that is important to overcome the adverse impact of market concentration and income inequality.